2016
DOI: 10.15376/biores.11.2.5265-5275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic Changes in Relative Humidity on the Sorption Hysteresis of Thermally Modified Spruce Wood

Abstract: Thermal modification of spruce wood (Picea abies L.) was conducted at three different temperatures (160, 200, and 240 °C) and treatment times (1, 3, and 5 h). The cyclic sorption experiments were performed for relative humidity changes of 30 to 85%. The equilibrium moisture content of the thermally modified wood was reduced up to 50% after treatment at 240 °C for 5 h. The sorption isotherms were described with the Guggenheim, Anderson, and De Boer (GAB) model. Cyclic sorption increased the monolayer capacity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…In both cases, a noticeable different adsorption curve, ie lower EMC values, were seen for the first cycle compared with the following two cycles. This indicates that a part of the EMC reduction effect resulting from the thermal treatment is reversible because of moisture sorption, in line with Hill et al (2012) and Majka et al (2016). Stronger drying 2.…”
Section: Sorption Propertiesmentioning
confidence: 78%
See 2 more Smart Citations
“…In both cases, a noticeable different adsorption curve, ie lower EMC values, were seen for the first cycle compared with the following two cycles. This indicates that a part of the EMC reduction effect resulting from the thermal treatment is reversible because of moisture sorption, in line with Hill et al (2012) and Majka et al (2016). Stronger drying 2.…”
Section: Sorption Propertiesmentioning
confidence: 78%
“…Earlier studies of the water vapor sorption behavior of TMW have shown significant reduction in hygroscopicity compared with UW controls, eg for Scots pine (Engelund et al 2010;Hill et al 2012), Sitka spruce (Hill et al 2010;Endo et al 2016) and Norway spruce (Pfriem et al 2010;Källbom et al 2016;Majka et al 2016). The preferential thermal degradation of hemicelluloses, which contain the highest concentration of water-accessible hydroxyl groups among the cell wall polymers (Runkel 1954;Runkel and Lüthgens 1956), reduces the number of water sorption sites in wood.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…180 and 220 °C, were set during the main phase of the modification. The duration of the main phase was 1 h. Majka et al (2016) showed that duration of the main phase of the laboratory-based thermal modification has no significant influence on mass loss and hygroscopic properties. The target temperature values were kept constant during the main phase.…”
Section: Thermal Modificationmentioning
confidence: 94%
“…Endo et al (2016) also report similar effects of heating at intermediate humidities, but in this case, the reduced EMC was largely recovered by moistening the wood in saturated water vapor at 25C. This temporary reduction in hygroscopicity is explained by the annealing-like physical aging of amorphous wood polymers, and is probably responsible for the unstable moisture sorption characteristics of dry-heated wood under cyclic changes in humidity (Majka et al 2016).…”
Section: Introductionmentioning
confidence: 69%